Apportioning prescribed fire impacts on PM2.5 among individual fires through dispersion modeling. (15th February 2020) - Huang, Ran; Qin, Momei; Hu, Yongtao; Russell, Armistead G.; Odman, M. Talat
Abstract: Prescribed burning is a prominent source of PM2.5 in the southeastern U.S. An air quality forecasting system called HiRes2 currently serves most areas in the southeastern U.S. to forecast PM2.5 concentrations one day in advance, including the impact of forecast prescribed burning activity. The output prescribed fire impact from the HiRes2 forecasting system is the combined impact of all the fires in the domain. When there are many fires close to each other, it is difficult to distinguish the ones that are more likely to lead to air quality issues. A novel source apportionment method, Dispersive Apportionment of Source Impacts (DASI), has been developed and applied to split the combined prescribed fire impact obtained from a chemical transport model (CTM) by using simulated fields from a dispersion model. Comparisons of apportioned fire impacts with single burn impacts simulated directly by the CTM show that DASI works well with large and small fires that do not have too much interaction with other fires. Individual fire impacts obtained by splitting the combined fire impacts from CTMs could help local land and air quality managers to evaluate which burns should be allowed or restricted based on their individual impacts on air quality and public health in areas of concern. Highlights: A new source apportionment method called DASI has been developed and evaluated. DASI is designed to split total prescribed fire impact into individual fire impacts. PM2.5 from prescribed fires in Georgia is about 80% primary and 20% secondary. DASI works well with large and small fires that do not have too much interaction. DASI could help to assess if a fire would affect air quality and public health.